Analisis Pengaruh Program Customer Relationship Management (CRM) Terhadap Kepuasan Pasien di RS PKU Muhammadiyah Yogyakarta - Siti Ayunda Mauliddina; Triani Marwati (Universitas Ahmad Dahlan, 2021)
uilding customer relationships is one of the keys to business success. The quality of a good relationship between customers and the company will contribute to increasing customer satisfaction. The purpose of this study was to examine the effect of the application of customer relationship management on patient satisfaction at PKU Muhammadiah Hospital Yogyakarta. This research was analitic observational by cross sectional approach. Data collection was carried out by distributing questionnaires to 120 service users of PKU Muhammadiah Hospital Yogyakarta. The data analysis method used is multiple linear regression analysis. Customer relationship management (CRM) which consists of people has an influence on patient satisfaction at PKU Muhammadiyah Yogyakarta Hospital with a probability value (p) 0.000 <0.05, process has an influence on patient satisfaction at PKU Muhammadiyah Yogyakarta Hospital with a probability value (p) 0.000 <0.05 and technology had an influence on patient satisfaction at PKU Muhammadiyah Hospital with a probability value (p) 0.009 <0.05, an increase in patient satisfaction RS PKU Muhammadiah Yogyakarta. To increase patient satisfaction, one way that can be done is to improve the quality of customer relationship program. To increase patient satisfaction, one way that can be done is to improve the quality program of customer relationships